Penggunaan Susu Kambing dan Putih Telur serta Koagulan Ie Asam Sunti pada Pembuatan Tahu Sutera (Tofu) - Anisa Putri; Salmyah Salmyah; Ratna Sari (Politeknik Negeri Lhokseumawe, 2023)
Silken tofu is a type of tofu that has a soft and compact texture. Ie sunti acid is a by-product of the process of making sunti acid which can be used as a coagulant. The disadvantage of the coagulant, namely sunti acid, is that it produces a silken tofu texture that is not compact. Therefore, cornstarch is added to the production of silken tofu to improve the texture quality of the silken tofu produced. This research aims to determine the effect of increasing coagulant concentration and adding goat's milk and egg white on the characteristics of silken tofu. This research method uses Central Composite Design (CCD) which is included in the Response Surface Method (RSM) and organoleptic methods. With coagulant concentration (2%, 4%, 6%, 8%, 10%) and goat milk volume (100 mL, 200 mL, 300 mL, 400 mL, 500 mL), as well as egg white weight (50 g, 55 g, 60 g, 65 g, 70 g). The results obtained optimal values, namely a goat's milk volume of 300 mL, an egg white weight of 60 g, and a coagulant concentration, namely sunti acid, of 6%, producing a silken tofu texture of 23.5 mm/sec, a pH level of 5 and a fat content of 3.25%. The volume of goat's milk, the weight of egg whites, and the concentration of sunti acid did not affect the color and taste of silken tofu but did affect the aroma of silken tofu